Making Digital Poetry: Writing with and through Spaces. - Magearu, Mirona (Journal of Literary Theory (18625290), 2012)
This article extends work on notions of space developed by media and poetry theorists. It particularly analyzes how contemporary technologies re-define the writing space of digital poetry making by investigating the configuration of this space in the writing of the digital poem. First, I acknowledge the permanent engagement of poetry with its writing spaces. In this respect, I delineate how the transition from oral to print and then to new media culture configure diverse forms of poetry which emerge in and with diverse writing spaces. In oral culture, for instance, poetry is created in an oral space that is the space in which the word is uttered and transmitted. Because the oral poet writes directly to the minds of the audience, the space of poetry writing becomes the space between the poet and his audience. With print culture, poetry is tied to page as a writing space. This space records the spoken words on the page in the form of script that becomes a poem only when readers encounter it. In new media culture, poetry relies on the use of various computer media in the composition, generation, or presentation of the text. The making of digital poetry integrates the zeros and the ones of the digital writing space. As a result, the writing space in which the poem is made manifest fosters a particular perception vis-à-vis the act of writing. Then, I bring up specific works from the early 1900s poetic experiments and the concrete poetry tradition. In this sense, I cite the French and Italian influential poets Stéphane Mallarmé, Guillaume Apollinaire, and Filippo Marinetti who raised awareness on the significance of space in the meaning making of their works. My study dedicates more space to the concrete poets' manifestos from the sixties who theorized the conceptual use of space in their poetries. I specifically analyze how in Eugen Gomringer's Silence space carries semantic meaning and is endowed with a dual function: it is a container and a contained element which brings words together and holds them. Based upon these theoretical considerations, I frame my understanding vis-à-vis the configuration of space in digital poetry. This article proposes the concept of ›trans-medial‹ space by re-fashioning Bolter's ›topographic writing.‹ In 1991 new media theorist David Jay Bolter traces the changing technologies of writing and associates the emergence of hypertext with the ›topographic‹ quality of digital writing: the mathematical arrangement of verbal ideas in visual spaces. My concept examines how digital poetry exists, emerges, and is experienced only within a digital space and how it conveys a perception of the writing space as multiple and changeable. This concept also provides a significant paradigm for thinking about the space(s) engaged in the making of digital poetry, insofar as I consider the spaces of the computer screen, source code, and code execution. I explicitly address questions regarding the configuration of space in digital poetry and the interspatial relationship between screen and source code spaces. This digital writing space is made of multiple spaces of encoding and decoding which interconnect with one another and give birth to an in-between space. The primary space is the source code where the poet installs the code which contains the script of the poem. This code has a meaningful existence only when it is encountered, received, and reconceived by the reader. Hence, there is also the screen space where the code becomes work only through the reader's access. Both spaces are transformative in the sense that they are physically in a morphing state: screen space evolves out of source code space. In this way, this digital writing space is a ›trans-medial‹ space: it forms itself as it self-transforms. My close reading of Brian Kim Stefans's digital poem, The Dreamlife of Letters, considers the dialectics between the spaces of the poem in its print, index, and onscreen performance versions and, therefore, epitomizes the significance of trans-medial space. The fact that the present technologies of writing call for the trans-medial quality of writing opens up new venues for the reading of the digital works by re-fashioning the concept of the writing space of our digitized world. Moreover, this ›trans-medial‹ approach to space expands the lines of continuity between poetry from oral culture, traditional print, and the present forms of digital expression. Such a perspective also reinforces the theoretical understanding of the close connections between literature and modern media.